VO2peak comparison of a treadmill vs. Cycling protocol in elite teenage competitive runners, cyclists, and swimmers - Marko, D.; Bahenský, P.; Snarr, R. L.; Malátová, R. (The Journal of Strength and Conditioning Research, 2022)
The purpose of this study was to compare the cardiorespiratory and metabolic responses of a maximal graded exercise test (GXT) on a treadmill and cycle ergometer in elite-level, youth competitive athletes. Thirty-one athletes (11 distance runners, 11 mountain-bike cyclists, and 9 long-distance swimmers) were randomly selected to complete either a running or cycling GXT on the first day, followed by the alternative 72 hours apart. The initial work rate for each GXT was set at 50% of the individuals' previously established Vo2peak to elicit fatigue within 8-12 minutes. For the treadmill protocol, speed was increased by 1 km·h-1 each minute, with a constant 5% grade, until volitional fatigue. Cycle ergometer work rate was increased by 30 W every minute until volitional fatigue or the inability to maintain proper cadence (i.e., 100 ± 5 rev·min-1). Throughout both testing sessions, Vo2peak, heart rate [HR] peak, breathing frequency (BF), tidal volume (VT), and minute ventilation (VE) were assessed and used to compare within-sport differences. Runners displayed a higher Vo2peak (~7%; d = 0.92), HRpeak (4%; d = 0.77), VE (6%; d = 0.66), and BF (12%; d = 0.62) on the treadmill vs. cycle. However, the cycling group demonstrated a greater Vo2peak (~8%; d = 0.92), VT (~14%; d = 0.99), and VE (~9%; d = 0.78) on the cycle, despite no change in HRpeak. For swimmers, the treadmill GXT elicited higher values in Vo2peak (~5%; d = 0.75), BF (~11.5%; d = 0.78), and HRpeak (3%; d = 0.69). Collectively, these findings indicate that exercise mode may greatly affect physiological outcome variables and should be considered before exercise prescription and athletic monitoring.